Rhodium‐Catalyzed Borylation/Protonation Tandem Reaction of Hydroxylated Diarylethynes. Issue 6 (5th April 2017) - Yang, Liting; Ma, Jinjin; Peng, Xiaomin; Wang, Danyang; Guo, Tao; Yuan, Bingxin; Li, Heng; Zhang, Panke; Yang, Guanyu
Abstract: The catalytic synthesis of trans ‐hydroxystilbenes has a great significance and value in synthetic chemistry and bioscience. To establish a versatile and efficient technology for such reactions, we successfully developed a novel and straightforward way for the construction of E ‐stilbene derivatives by a rhodium‐catalyzed borylation/protonation tandem reaction using H2 O as the green hydrogen source. Various E ‐stilbene derivatives were synthesized with up to 85 % yield. Abstract : As simple as wate r! The construction of E ‐stilbene derivatives by a rhodium‐catalyzed borylation/protonation tandem reaction using H2 O as the green hydrogen source has been reported. Various E ‐stilbene derivatives were synthesized with up to 85 % yield.